2020
DOI: 10.30585/jrems.v3i1.555
|View full text |Cite
|
Sign up to set email alerts
|

Can cryptocurrencies be a safe haven during the novel COVID-19 pandemic? Evidence from the Tunisian Stock Market

Abstract: In this paper, we discuss the behavior of stock market returns in Tunisia during the COVID-19 outbreak. Using the OLS regression, we find that Bitcoin act as a hedge and Ethereum as a diversifier for Tunisia’s stock market before the COVID-19 outbreak; however, Bitcoin and Ethereum cannot generate benefits from portfolio diversification and hedging strategies for financial investors during the COVID-19. Moreover, Dash, Monero, and Ripple act as hedges before the COVID-19 outbreak and as diversifiers during thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 19 publications
1
13
1
Order By: Relevance
“…This result is therefore aligned with that of Baur and Lucey ( 2010 ), who suggested that gold acts as a safe-haven in extreme stock market conditions, In fact, Baur and McDermott ( 2010 ) confirmed the safe-haven property of gold for the US and big stock markets in Europe, and more recently Ji et al ( 2020 ), who indicated that gold has remained robust (strong) as a safe-haven asset during the COVID-19 pandemic. However, this result contradicts that of Jeribi and Snene-Manzli ( 2021 ), who indicated that gold was neither hedge nor a safe haven for the Tunisian investors during the COVID-19 outbreak. It also contradicts the results of Shahzad et al ( 2019 ) who found that gold is a weak safe haven and Cheema et al ( 2020 ) who found that gold fails to protect the investors’ wealth during the COVID-19 pandemic.…”
Section: Estimation Resultscontrasting
confidence: 76%
See 1 more Smart Citation
“…This result is therefore aligned with that of Baur and Lucey ( 2010 ), who suggested that gold acts as a safe-haven in extreme stock market conditions, In fact, Baur and McDermott ( 2010 ) confirmed the safe-haven property of gold for the US and big stock markets in Europe, and more recently Ji et al ( 2020 ), who indicated that gold has remained robust (strong) as a safe-haven asset during the COVID-19 pandemic. However, this result contradicts that of Jeribi and Snene-Manzli ( 2021 ), who indicated that gold was neither hedge nor a safe haven for the Tunisian investors during the COVID-19 outbreak. It also contradicts the results of Shahzad et al ( 2019 ) who found that gold is a weak safe haven and Cheema et al ( 2020 ) who found that gold fails to protect the investors’ wealth during the COVID-19 pandemic.…”
Section: Estimation Resultscontrasting
confidence: 76%
“…In their study, they concluded that the stock market is highly unpredictable and volatile due to the instability and economic damages caused by this pandemic. Moreover, Jeribi & Snene-Manzli ( 2021 ), Baig et al ( 2020 ), Al-Awadhi et al ( 2020 ), Jeribi et al ( 2020 ), and Bader ( 2020 ) stated that the growing number of confirmed COVID-19 cases and deaths has a negative impact on stock markets.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Akrofi and Antwi (2020) studied the African energy sector and found a considerable downturn after the COVID-19 pandemic. Furthermore, Jeribi and Manzli (2021) analyzed the post-COVID-19 behavior of the Tunisian stock market and found a strong relationship between the number of confirmed cases (and deaths), and stock market performance. In essence, the referred as volatility, which is an essential component for the smooth functioning of the market, especially from an investor's perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study of the safe-haven properties of global equities against commodities (gold and crude oil) and cryptocurrency (Bitcoin) by Disli et al (2021) found that gold, oil and Bitcoin do not exhibit safe-haven characteristics. Jeribi and Snene Manzli (2020) studied Bitcoin against Tunisian stock market indices and found that Bitcoin acted as hedge and Ethereum as a diversifier before the COVID-19 outbreak. However, during the covid-19 period neither acted as a diversifier or hedge.…”
Section: Literature Reviewmentioning
confidence: 99%